Proceso atención de enfermería en adolescente con traumatismo testicular derecho. - Álvarez Sánchez, Kevin Daniel (2022)
Injuries to the scrotum and testicles can have significant consequences, testicular trauma is a rare injury that can occur at any age, especially from adolescence and is caused by trauma to the testicles on the pubic arch, which can cause various lesions of the testicular tissues and adjacent structures: male infertility due to spermatogenesis disorders, autoimmune mechanisms or damage to the posterior vas deferens, the same that in very serious cases end in inguinal orchiectomy. The following clinical case deals with a patient "Nursing care process in adolescent with right testicular trauma", characterized by pain in the inguinal region, accompanied by pubic edema, thermal rise, which occur as a result of a blow by a contused object at the right scrotal region level. The main objective of applying the Nursing Care Process is to recognize the key factors for the early diagnosis of complications that may occur before, during and after the process, highlighting the nursing diagnosis, to execute activities with the health team staff. multidisciplinary in a rapid and timely manner, in order to detect the absence of reliable clinical and radiological signs except within the first six hours of the onset of symptoms, which are usually inflammation and edema, and the signs include discoloration and weakening of the scrotum that with a timely intervention is the only alternative to preserve the gonads.